2011
DOI: 10.1007/s00299-011-1026-x
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the DNA C-values of the genome size-standards used in plant flow cytometry to choose the “best primary standards”

Abstract: Flow cytometry (FCM) techniques have enabled characterization of the genome size for various plant species. In order to measure the nuclear genome size of a species, reference standards with well-established DNA content are necessary. However, different 2C-values have been described for the same species used as reference standard. This fact has brought about inaccurate genome measurements, making relevant the establishment of optimal DNA reference standards for plant cytometric analyses. Our work revisited the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
47
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 66 publications
(52 citation statements)
references
References 37 publications
0
47
0
2
Order By: Relevance
“…1c) was identical to that evidenced by Clarindo et al (2013). Praça-Fontes et al (2011) compared the DNA content measurement of eight plants widely used as primary standards in FCM approaches by applying each separately as primary standard, in a cascade-like manner. In conclusion, these authors reported that S. lycopersicum is a suitable primary reference standard for FCM assessments in plants.…”
Section: Fcm and Cytogenetic Analysesmentioning
confidence: 99%
See 2 more Smart Citations
“…1c) was identical to that evidenced by Clarindo et al (2013). Praça-Fontes et al (2011) compared the DNA content measurement of eight plants widely used as primary standards in FCM approaches by applying each separately as primary standard, in a cascade-like manner. In conclusion, these authors reported that S. lycopersicum is a suitable primary reference standard for FCM assessments in plants.…”
Section: Fcm and Cytogenetic Analysesmentioning
confidence: 99%
“…These materials were used as source of leaf fragments for somatic embryo induction, based on method of van Boxtel and Berthouly (1996), as well as for FCM assessments. Seeds of Solanum lycopersicum L. Stupické (2C=2.00 pg, Praça-Fontes et al 2011) were kindly supplied by Dr. Jaroslav Doležel (Experimental Institute of Botany, Czech Republic), and used as primary standard for FCM analysis.…”
Section: Plant Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Myrsine parvifolia was collected in a forest remnant located in Guarapari municipality, ES, Brazil (20°36'15"S – 40°25'27"W), characterized as coastal sandy plains vegetation (Restinga) at sea level. Leaves and fruits of Solanum lycopersicum L. and Pisum sativum L. (internal standards for flow cytometry – FCM, 2C = 2.00 pg and 2C = 9.16 pg, respectively, Praça-Fontes et al 2011) were supplied by Dr. Jaroslav Doležel (Experimental Institute of Botany, Czech Republic).…”
Section: Methodsmentioning
confidence: 99%
“…The suspensions were processed and stained following Otto (1990) and Praça-Fontes et al (2011) and analyzed with the flow cytometer Partec PAS II/III (Partec GmbH). Myrsine genome size was measured by multiplying the 2C value of the internal standard using the fluorescence intensity corresponding to G 0 /G 1 nuclei peak.…”
Section: Methodsmentioning
confidence: 99%